Avelumab, an IgG1 anti-PD-L1 Immune Checkpoint Inhibitor, Triggers NK Cell-Mediated Cytotoxicity and Cytokine Production Against Triple Negative Breast Cancer Cells - Juliá, Estefanía Paula; Amante, Analía; Pampena, María Betina; Mordoh, José; Levy, Estrella Mariel (Frontiers in Immunology, 2018)
The standard treatment for Triple Negative Breast Cancer (TNBC) patients is cytotoxic chemotherapy, but it is restricted since the duration of response is usually short. Blocking the PD-1/PD-L1 pathway through monoclonal antibodies (mAbs) appears to be a promising therapeutic strategy for TNBC patients. Avelumab is a human IgG1 anti-PD-L1 mAb being tested in clinical trials that may also trigger antibody-dependent cell-mediated cytotoxicity (ADCC) against cancer cells as an additional antitumor activity. In the present work, we studied in vitro Avelumab-mediated ADCC against a panel of TNBC cells with different PD-L1 expression using peripheral blood mononuclear cells (PBMC) or purified NK cells from healthy donors. We determined that Avelumab significantly enhanced NK-cell mediated cytotoxicity against TNBC cells and that tumor cells expressing higher levels of PD-L1 were more sensitive to Avelumab-mediated ADCC. IFN-γ treatment upregulated PD-L1 expression in tumor cells but had a variable impact on Avelumab-mediated ADCC, which could be related to the simultaneous effect of IFN-γ on the expression of NK cell ligands. Moreover, IL-2 and IL-15 stimulation of NK cells enhanced Avelumab-triggered cytokine production and degranulation along with increased lytic activity against tumor cells. Improving the treatment of TNBC remains still a considerable challenge. This in vitro study suggests that Avelumab-mediated ADCC, independently of the blockade of the PD-1/PD-L1 pathway, could be a valuable mechanism for tumor cell elimination in TNBC. Avelumab combination with immunomodulators such as IL-15 or IL-2 could be taken into consideration to increase the therapeutic efficacy of Avelumab in TNBC.